Benchmarking solid oxide electrolysis cell-stacks for industrial Power-to-Methane systems via hierarchical multi-scale modelling. (1st July 2022) - Wehrle, Lukas; Schmider, Daniel; Dailly, Julian; Banerjee, Aayan; Deutschmann, Olaf
Graphical abstract: Highlights: Comprehensive validation and parametrization of 2D single cell and 3D stack models. Specific threshold conversions of 80% (ESC) and 75% (CSC) which maximize efficiency. Performance boost for CSC and losses for ESC design under pressurized conditions. Feasible stack operation only at thermoneutral to moderately exothermic conditions. CSC-stack reaches doubled H2 -output at 700 °C compared to ESC-stack at 850 °C. Abstract: Power-to-Gas (PtG) is prognosticated to realize large capacity increases and create substantial revenues within the next decade. Due to their inherently high efficiencies, solid oxide electrolysis cells (SOECs) have the potential to become one of the core technologies in PtG applications. While thermal integration of the high-temperature SOEC module with downstream exothermic methanation is a very potent concept, the performance of SOECs needs to be boosted to amplify the technologies impact for future large-scale plants. Here, we use a combined experimental and modelling approach to benchmark commercial electrolyte- (ESC) and cathode-supported cell (CSC) designs on industrial-scale planar SOEC stack performance. In a first step, comprehensive electrochemical and microstructural analyses are carried out to parametrize, calibrate and validate a detailed multi-physics 2D cell model, which is then used to study the cells' behaviour in detail. The analysis reveals that there exists a cell-specific threshold steam conversion of ∼80% for the ESC and ∼75% for the CSC design, which represents a maximum of the total (heat plus electrical) electrolysis efficiency. Moreover, while the ESC-design suffers from performance reductions under pressurized conditions, considerable performance increases of ∼9% at 20 atm (700 °C, 1.35 V) compared to atmospheric pressure are predicted for the CSC design, showcasing a unique advantage of the CSC cell for process integration with the catalytic methanation. Subsequently, based on a 3D stack model, a scale-up to the industrial stack size is conducted. To comparatively assess stack performances under application-oriented conditions, optimization studies are carried out for 150-cell stack units based on the two cell designs individually. When optimally selecting the stack operation points, the model predicts the CSC-based stack to reach a high capacity up to 36.6 kW (∼10.6 Nm 3 H2 h −1 ) at 1.35 V and 700 °C, whilst ensuring reasonably low temperature gradients (<10 K cm −1 ) and sweep gas cooling requirements (<30 sccm cm −2 ). Thus, CSC-design stacks incorporating such a highly active cell design can be expected to further boost the competitiveness of high-temperature electrolysis in PtG plant concepts.